Turning Opposition into Support to Immigration: The Role of Narratives - Cristina Cattaneo; Daniela Grieco (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2020)
The way we collectively discuss migration shapes citizens' perceptions of migrants and their influence on our society. This paper investigates whether a narrative about the positive impact of immigrants on the hosting economy affects natives' behaviour towards migrants. To shed light on the underlying mechanism, we present a simple theoretical framework that models the relationship between beliefs, attitude and behaviour and identifies the sequential channels through which a narrative might be useful in changing attitude and behaviour. We test its predictions through an online survey experiment, where we deliver UK natives a favourable narrative about migrants. Treated subjects revise their beliefs about migrants and exhibit significantly more positive self-reported attitudes and more pro-migrant behaviour. Moreover, they update beliefs in a way that gives support to the existence of confirmation bias.
Keywords: C90; D83; F22; J15; Z15; 330; Immigration; Survey experiment; Narrative; Attitudes; Beliefs